An analysis of the effectiveness of the infrastructure delivery management system in the South African government - Melete, Refiloe Minah (University of the Witwatersrand, Johannesburg, 2024)
Governments face inherent obstacles in the provision of infrastructure at a global level. The decline or degradation of societal infrastructure and the limited accessibility to public services for the entire South African population can be ascribed to factors such as inadequate provisioning and upkeep of infrastructure. The adverse implications of construction project failures attributed to a variety of factors, such as delayed provision and increased costs directly impact economic well-being of individuals. South Africa's government is guided by a complicated system of broad and sector-specific policies with distinct objectives. The South African government has implemented various strategies and initiatives to enhance infrastructure delivery, and the effectiveness of developing infrastructure delivery methods for public infrastructure initiatives remains questionable. Despite substantial study on infrastructure delivery difficulties, there remains a paucity of complete evidence about the efficacy of certain infrastructure delivery changes. Previous research identified by academic research has mostly focused on challenges such as public protests, corruption, delays in service delivery, inefficient operations, and inadequate quality management, leaving a knowledge gap about the overall efficacy of various delivery reforms and restricting insights into broader system performance. The South African government has adopted the infrastructure delivery management system (IDMS), a comprehensive approach that integrates planning, implementation ,monitoring and maintenance of infrastructure projects, as its preferred framework for implementation. The system’s effectiveness has not been tested. To close this gap the research analyses the effectiveness of IDMS in infrastructure provision. The study’s objectives were achieved through a qualitative methods, involving in-depth interviews and thematic and content analysis was employed. A purposive selection process was employed to choose a cohort consisting of senior managers, project managers, and external service providers. This resulted in a total of 100 individuals who were chosen to participate in the study. Interviews were conducted with these individuals. A response rate of 72% was attained, indicating a high level of participant engagement and data reliability. The study posits that various infrastructure delivery methods have been tried by both emerging and developed nations, but with limited success rate. Without a universally diverse and integrated infrastructure delivery, the current state of deterioration will continue. South Africa, as a developing nation, has the potential to reap substantial benefits by placing emphasis on the preservation, expansion, and enhancement of its infrastructure delivery. The findings of the study suggest that there are constraints with the current delivery system on adherence to regulations and implementation of system components. The study reveal a significant prevalence of inconsistencies in the application of the system. Lack of transparency in government policies impedes their implementation, causing a multitude of obstacles that contribute to additional project delays. The project's effectiveness is impeded by its inability to run efficiently due to the impact of the changing political environment on laws and industry reform. The study identified significant relationship between competency and governance, and how each impacts the effectiveness of the delivery management system. Consistently assessing policy iii and enhancing the implementation of legislation is vital for properly harnessing industry principles and endeavours. In order to achieve a balanced approach and encourage stakeholder ownership and commitment, collaborative interaction with industry professionals is essential. Improving infrastructure delivery requires implementing an integrated framework with clear goals, enhancing governance structures, a well-defined capacitation strategy to implement the framework, clearly defined roles and responsibilities. and promoting collaboration among government stakeholders for decision making and defined timelines for processing decisions in infrastructure delivery. Additionally, it is essential to streamline processes and cultivate technical expertise within infrastructure departments. The presence of strong governance structures, streamlined processes, and efficient human resource management are strong factors recommended for an integrated delivery framework. This study offers a significant contribution to the current body of literature on public sector infrastructure delivery methods. The research offers study offers valuable insights and contributes to creating efficient and sustainable infrastructure delivery methods and serves as a guiding resource for developing government policies and decision making.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy , In the Faculty of Engineering and the Built Environment , School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Effectivenes; reform; IDMS; Infrastructure delivery; public service; SDG-8: Decent work and economic growth